Pengaruh Promosi, Harga, Dan Online Costumer Review Terhadap Minat Beli Tik-Tok Shop - Ghafur, Nurvikrih Choliluddin; Basalamah, Muhammad Ridwan; Khalikussabir, Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research aims to determine the extent of the influence of promotions, prices, and online customer reviews on purchasing interest at the Tik-Tok shop. The population in this study was 565 students from the Faculty of Economics and Business, Islamic University of Malang and the sample used in this study used the Slovin approach so that a sample of 85 was obtained. Testing was carried out using IBM SPSS version 25. It was found that promotions, prices and online customer reviews had a positive effect. and simultaneously significant to purchasing interest in the Tik-Tok shop. Meanwhile, partially promotion has a positive and significant effect on buying interest in the Tik-Tok shop, price has a positive and significant effect on buying interest in the Tik-Tok shop, online customer reviews have a positive and significant effect on buying interest in the Tik-Tok shop. Keywords: Purchase Interest, Promotions, Prices, And Online Customer Reviews